Ciprofloxacin, diclofenac, ibuprofen and 17α-ethinylestradiol differentially affect the activity of acetogens and methanogens in anaerobic communities - Silva, Ana Rita Pereira (2020)
Pharmaceutical compounds end up in wastewater treatment plants but little is known on their effect towards the different microbial groups in anaerobic communities. In this work, the effect of the antibiotic Ciprooxacin (CIP), the non-steroidal anti-inammatory drugs Diclofenac (DCF) and Ibuprofen (IBP), and the hormone 17-ethinylestradiol (EE2), on the activity of acetogens and methanogens in anaerobic communities, was investigated. Microbial communities were more affected by CIP, followed by EE2, DCF and IBP, but the response of the different microbial groups was dissimilar. For concentrations of 0.01 to 0.1 mg/L, the specic methanogenic activity was not affected. Acetogenic bacteria were sensitive to CIP concentrations above 1 mg/L, while DCF and EE2 toxicity was only detected for concentrations higher than 10 mg/L, and IBP had no effect in all concentrations tested. Acetoclastic methanogens showed higher sensitivity to the presence of these micropollutants, being affect by all the tested pharmaceutical compounds although at different degrees. Hydrogenotrophic methanogens were not affected by any concentration, indicating their lower sensitivity to these compounds when compared to acetoclasts and acetogens.